2008
DOI: 10.1002/cssc.200800069
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Solid Catalysts for the Selective Use of Glycerol as a Natural Organic Building Block

Abstract: Glycerol is the main co-product of the vegetable oils industry (especially biodiesel). With the rapid development of oleochemistry, the production of glycerol is rapidly increasing and chemists are trying to find new applications of glycerol to encourage a better industrial development of vegetable oils. In this Review, attention is focused on the selective use of glycerol as a safe organic building block for organic chemistry. An overview is given of the different heterogeneous catalytic routes developed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(72 citation statements)
references
References 103 publications
(116 reference statements)
2
69
0
1
Order By: Relevance
“…Several other examples have been gathered in a review by Diaz-Alvarez et al [6]. Studies by Jérôme and Gu [7][8][9], have shown that, in some reactions, such as the Aza-Michael reaction of p-anisidine and the Michael reaction of indole, glycerol used as solvent is capable to achieve yields up to 80% under catalyst-free conditions, these yields being higher than those obtained with usual solvents. The same research group has developed a series of catalysts combined with sugarbased-surfactants of organic substrates which favors mass transfer of organic substrates and limits the undesired reactivity of glycerol [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several other examples have been gathered in a review by Diaz-Alvarez et al [6]. Studies by Jérôme and Gu [7][8][9], have shown that, in some reactions, such as the Aza-Michael reaction of p-anisidine and the Michael reaction of indole, glycerol used as solvent is capable to achieve yields up to 80% under catalyst-free conditions, these yields being higher than those obtained with usual solvents. The same research group has developed a series of catalysts combined with sugarbased-surfactants of organic substrates which favors mass transfer of organic substrates and limits the undesired reactivity of glycerol [10].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] With the decline of petrochemical resources accompanied by a continuing increase in oil prices, research has been intensively focused on biomass. [3,4] Glycerol is an abundant renewable resource obtained in large quantities from biomass as a by-product of the transesterification of triglycerides or in alternative from the fermentation of glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, glycerol is a highly functionalized molecule and a large number of useful compounds can be obtained through its oxidation, hydrogenolysis, dehydration, esterification, and/or polymerization. [1,2] Many studies have recently been devoted to the selective oxidation of glycerol, using gold as the catalyst. In particular, it has been demonstrated that, under the right circumstances, Au can be more active and selective towards glyceric acid than Pd or Pt.…”
Section: Introductionmentioning
confidence: 99%
“…Other uses include production of explosives, dyes, polymers, lubricants, printing ink and papers in the chemical industry. [5][6][7][8] More recently it has been used as a building block and solvent in organic synthesis. [9][10][11] Biologically, it is currently used as a cryoprotectant of different biological materials, in purification of proteins and enzymes, in bacterial cultures, and in the production of bioplastics, among other uses.…”
Section: Introductionmentioning
confidence: 99%
“…6 To make biodiesel economically viable, new and efficient routes for transforming glycerol into higher value products must be developed. [5][6][7][8] Although most biodiesel physico-chemical properties have close resemblance to petrol diesel, freezing problems and increase in viscosity at low temperatures, besides low resistance to oxidation, render it inferior in comparison to petrol diesel. The addition of bioadditives derived from glycerol could lead to an improvement in biodiesel efficiency and glycerol valorization, thus decreasing the total cost biodiesel production making it an even more attractive fuel.…”
Section: Introductionmentioning
confidence: 99%